POWER, DISCOURSE, AND THE ERASURE OF REVOLUTION: A POSTCOLONIAL READING OF SYRIA’S STRUGGLE FOR FREEDOM - Sati, Dean (Young Scholars Grinchenko – Seton International Journal, 2026)
This paper examines how the democratic aspirations of the Syrian uprising were gradually erased through domestic and international discourse. It argues that narratives produced by the Assad regime and reinforced by global actors reframed the uprising from a movement for freedom and dignity into a conflict defined by terrorism, sectarianism, and instability. Drawing on the work of Michel Foucault and Edward Said, the paper shows how power operates through language and representation, shaping how conflicts are understood and responded to. Writing from an Arab American perspective, it also considers how orientalist assumptions continue to influence Western interpretations of Middle Eastern resistance movements. Ultimately, it argues that the erasure of democratic aspirations in Syria is not only the result of state violence, but also of the narratives that shape how the conflict is understood globally.